Pengembangan Media Smart Apps Creator untuk Pembelajaran Wawancara di Sekolah Dasar - Herlina, Septa Khairani; Kurniaman, Otang; Putra, M. Jaya Adi (Lembaga Yasin AlSys, 2023)
This research aims to produce interactive multimedia development products on human digestive system material in elementary schools. The method used in this research is the R&D (Research and Development) development method with the 4D model. There are 4 stages carried out, namely definition, planning, development, distribution. In this research, researchers only carried out the development stage. The media developed by researchers was validated by 2 media experts. The practicality can be seen from the small group limited trial questionnaire. The data collection technique used by researchers in this research was a questionnaire. The data obtained from this data collection is then processed using quantitative analysis and description techniques. Based on the validation results of the smart apps creator media which was developed with very valid criteria with an average percentage of 95.93%. Meanwhile, the practicality of this media is based on the average percentage score of teacher response questionnaires of 93.63% and the average percentage of students' practicality score of 86.56%. From the research results, it can be concluded that the smart apps creator media in the interview material criteria is valid and practical to use for learning.